¿Es posible el diálogo entre filosofía e historia? El caso O’Gorman - Alfonso Mendiola (Nuevo mundo - Mundos Nuevos, 2012)
This essay deals with the impact of Heidegger’s philosophy on the historiographical works of Edmundo O'Gorman. To explain how much philosophical thinking has been present in the task of the historian, it is necessary to reassess the changes in the nature and role of philosophy in the late nineteenth and early twentieth centuries. This philosophy emerges from the so-called "conscience of historicity." In the path that runs from Dilthey to Heidegger via Husserl, one can notice the need to abandon the Western metaphysical elaboration, unable to take historicity into account. The attempt to appropriate historicity requires to detach oneself from the cognitive approach characterizing the philosophy of the eighteenth century, and to move to a philosophy of facticity or experience. Being and Time comes from Heidegger’s previous courses, which are discussed in this essay in relation with O’Gorman historiography.